PENGEMBANGAN WORDLESS PICTURE BOOK UNTUK PEMBELAJARAN BERCERITA KELAS II SEKOLAH DASAR - Syifa Monica (Universitas Negeri Medan, 2022)
Abstract: This research and development aim to produce a product in the form of a wordless picture book for teaching storytelling for the second grade of elementary school. The method used in this research is research and development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Respondents in this study consisted of media experts, media experts for images for children, and material experts. Due to the Covid-19 pandemic, user trials can only be carried out on a one-to-one trial consisting of three grade II elementary school students who live close to the researcher. Data collection techniques used in this study were interviews, observation, and questionnaires. The test results for developing wordless picture books were obtained 91.07% for media experts, 100% for material experts, 100% for picture media experts for children. 100% user trial results for the one-to-one stage. This shows that the wordless picture book developed is included in the “very good” category so it is suitable for use in teaching storytelling for class II Elementary School.Keywords: Wordless Picture Book, teaching storytellingAbstrak: Penelitian dan pengembangan ini bertujuan untuk menghasilkan produk berupa buku bergambar tanpa kata untuk pembelajaran bercerita kelas II sekolah dasar. Metode yang digunakan dalam penelitian ini adalah penelitian dan pengembangan (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Responden dalam penelitian ini terdiri dari ahli media, ahli media gambar untuk anak, dan ahli materi. Dikarenakan adanya pandemi Covid-19, uji coba pengguna hanya dapat dilaksanakan pada uji coba one to one yang terdiri dari tiga peserta didik kelas II sekolah dasar yang berdomisili dekat dengan peneliti. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi, dan kuesioner. Hasil uji coba pengembangan buku bergambar tanpa kata diperoleh 91,07 % untuk ahli media, 100% untuk ahli materi, 100% untuk ahli media gambar untuk anak. Hasil uji coba pengguna 100% untuk tahap one to one. Hal tersebut menunjukkan bahwa buku bergambar tanpa kata yang dikembangkan termasuk ke dalam kategori “sangat baik” sehingga layak digunakan dalam pembelajaran bercerita kelas II Sekolah Dasar.Kata Kunci: Wordless Picture Book, Pembelajaran Bercerita